RECEPTIVE THEOLOGICAL LEARNING IN AND FROM THE ASIAN BISHOPS - Sheveland, John N (Asian Horizons, 2016)
This article argues three points concerning the Federation of Asian Bishops’ writings on theological method. First, because North Atlantic ecclesial and academic communities stand to learn much from their Asian Christian brothers and sisters, the relative invisibility of the latter in North Atlantic contexts represents a missed opportunity to learn from the resources available in World Christianity, specifically Asian theologies. Second, through their own distinctively Asian patterns of receptivity in theological learning, the bishops and their trusted theologians exemplify many key tenets of Receptive Ecumenism and thus warrant study by practitioners of receptive theological disciplines like Comparative Theology, Scriptural Reasoning, and Receptive Ecumenism. Third, in answer to the question, ‘what are the conditions for the possibility of receptive learning?,’ the article proposes that a psychology of faith development can dispose or inhibit one from receptivity. Evidence is adduced in support of the Asian bishops exemplifying what James Fowler would call a Stage 5 conjunctive faith, which may, in the bishops’ writings, signify a fresh performance of catholicity.